PENGEMBANGAN MEDIA PEMBELAJARAN DESAIN TEMATIK: UPAYA MENINGKATKAN HASIL BELAJAR SISWA DAN KEMAMPUAN PENGELOLAAN KELAS BAGI GURU SD DALAM IMPLEMENTASI KURIKULUM 2013 - Chrisnawati, Henny Ekana; Usodo, Budi; Pramesthi, Getut; Sutopo, Sutopo (Universitas Sebelas Maret, 2016)
Abstract: Integrated thematic learning is learning approach that associates some positive aspects in the intra and inter-subject. The integration properties is based on the theme as a binding relationship between matters and there is no separation between the material and subjects, require management setting of learning from the teachers. For that purpose, the aims of this program is to develop a media learning of elementary school students in the implementation of the curriculum 2013 in improving student learning outcomes and assisting elementary school teachers’ in designing teaching and learning activities in the classroom. The software that used is macromedia flash mx, because macromedia flash mx is one of animation software that can be used as a fun media learning and easier software for student to interact with the learning experience.The method used this research is a RnD Thiagarajan model, ie, Define, Design and Develop. The result of the development of the media learning was tested on a limited basis in elementary school student grade IV SD II Al Abidin and SD Warga Surakarta. The results of this research are (1) Media learning have been developed with implementing the 4D Thiagarajan, (2) The results of the content validation, a media learning with Macromedia Flash application are fit can be used with the revision, and the results of the assessment, indicating the category of eligibility amounting as 80 .825% (3) The reliability of the observation of students' response and instructional media development results, showing good agreement category (75.5%), (4) Learning outcomes showed 88% of students have a score above KKM school.Keywords: Thematic design, RnD, Macromedia Flash